﻿Le Père Couturier au Québec (1940-1941) : un vent de liberté - Brunet-Weinmann, Monique (RACAR : Revue d'art canadienne / Canadian Art Review, 1987)
Since the Paris-Paris exhibition at the Centre Pompidou in Paris (1981), Father Marie-Alain Couturier has been recognized as an important artistic entrepreneur, who invited the most important modern artists to work for the Catholic Church, regardless of their belief or ideology. Father Couturier spent some time in the province of Quebec and deeply influenced its artistic milieu, particularly during his first two stays (28 March-30 May 1940 and 12 December 1940-June 1941). The author deals with the ideas expressed by Couturier in lectures and their consequences.When Charles Maillard, the conformist director of Montreal’s Ecole des Beaux-Arts, introduced Father Couturier to the press on 29 March 1940, he specified that Couturier had come to direct studio courses in religious art as applied to church liturgy and not to give lectures. In Father Couturier’s view, however, religious art was not distinct from other forms of art. When he addressed the public in his lectures, this passionate modernist’s free speech seemed to shake the neo-classical columns of the Ecole des Beaux-Arts and the foundations of Montreal’s academic establishment. Father Couturier also sought to put the “revolutionary ideas” he articulated so well in his lectures into practice. With Jean-Marie Gauvreau, he planned the short-lived Religious Art Workshops at the Ecole du Meuble. He also organized the important Exposition d’artisanat religieux (June 1941), where modern Canadian works were shown to the public. In association with the Société d’art contemporain he mounted the celebrated Exposition des Indépendants in Quebec City to advance the cause of “living art” and “freedom in the arts.” He criticized “the sterility of academic solutions” and, implicitly, Charles Maillard.The consequences of Father Couturier’s ideas and actions were felt well beyond his brief physical presence in Montreal. The “Maillard affair” and the “Borduas affair” were among these consequences.